Avaliação microeconômica do comportamento de investidores frente às alterações de condições de mercado: os determinantes da não racionalidade dos investidores no mercado de fundos brasileiros - Fernandez Gonzalez, Ramon Francisco (2015)
In this paper we seek to identify the determinants of demand for mutual funds in Brazil through the logit model, which is widely used in the theory of industrial organizations. Whenever possible we perform 'links' with the main concepts of behavioral finance. Thus, we clarify the main variables that impact variations of 'market share' in the mutual funds industry. We conclude that the main indicators observed by investors at the time of decision-making, are the CDI, inflation, the real interest rate, the variation of the dollar and the stock market, on the other hand the accumulated return of the last three months is factor decisive for investors to apply or redeem an investment fund. Risk variables and expected return we thought to have a strong impact, not significant for variations of 'share'.